EFFECT OF CORAL GONIOPORA IN COMPARISON WITH CORAL APATITE TOWARDS HUMAN DENTAL PULP STEM CELLS MINERALIZATION ACTIVITIES: EFEK CORAL GONIOPORA DIBANDINGKAN DENGAN CORAL APATITE TERHADAP AKTIVITAS MINERALISASI SEL STEM PULPA GIGI - Rachmi Fanani Hakim; Endang Winiati Bachtiar; Nurtami Soedarsono (Dentika: Dental Journal, 2012)
Challenging approach in tissue engineering for dentin regeneration is focused upon the application of a scaffold on an open pulp enabling odontoblast-like cells to grow into the scaffold and to convert them into dentin-like substance. Coral was chosen as a scaffold because of its good biocompatibility and resorbability. The species of marine invertebrates exploited in medical applications are Members of Porites and Goniopora. Coral goniopora is most marine invertebrata found in Indonesia’s marine. Coral apattite, an osteoconductive synthetic bone graft substitute material, is manufactured by the hydrothermal conversion of the calcium carbonate skeleton of coral to hydroxyapattite in the presence of ammonium phosphate preserving the original porous structure which is similar to that of bone. The aim of study was to investigate the effect of Coral goniopora and coral apattite as a potential scaffold on dental pulp mineralization activity. In vitro DPSCs mineralization activity was measured by von Kossa staining for calcium deposit identification. The result that Coral apattite increased more calcium deposited identification than coral goniopora. Calcium deposited on dental pulp stem cells are marker for mineralized dental pulp stem cells (DPSCs). Mineralized DPSCs are marker for odontoblast diferentiation and maturation. In conclusion, these observations demonstrated that co-cultured coral apattite and DPSCs induced a better mineralization activity than those cultured with Coral goniopora.